Investigating a Boronate‐Affinity‐Guided Acylation Reaction for Labelling Native Antibodies. Issue 17 (19th February 2022) - Adak, Avijit K.; Huang, Kuan‐Ting; Liao, Chien‐Yu; Lee, Yuan‐Jung; Kuo, Wen‐Hua; Huo, Yi‐Ren; Li, Pei‐Jhen; Chen, Yi‐Ju; Chen, Bo‐Shiun; Chen, Yu‐Ju; Chu Hwang, Kuo; Wayne Chang, Wun‐Shang; et al.
Abstract: The excellent molecular recognition capabilities of monoclonal antibodies (mAbs) have opened up exciting opportunities for biotherapeutic discovery. Taking advantage of the full potential of this tool necessitates affinity ligands capable of conjugating directly with small molecules to a defined degree of biorthogonality, especially when modifying natural Abs. Herein, a bioorthogonal boronate‐affinity‐based Ab ligand featuring a 4‐(dimethylamino)pyridine and an S‐aryl thioester to label full‐length Abs is reported. The photoactivatable linker in the acyl donor facilitated purification of azide‐labelled Ab (N3 ‐Ab) was quantitatively cleaved upon brief exposure to UV light while retaining the original Ab activity. Click reactions enabled the precise addition of biotin, a fluorophore, and a pharmacological agent to the purified N3 ‐Abs. The resulting immunoconjugate showed selectivity against targeted cells. Bioorthogonal traceless design and reagentless purification allow this strategy to be a powerful tool to engineer native antibodies amenable to therapeutic intervention. Abstract : Adding function : A boronate‐affinity ligand and an S‐aryl thioester have been developed that are capable of labelling native Abs with a functional molecule. Additionally, a photoactivatable crosslinker allows purification of labelled Abs in a reagentless manner, thereby producing homogeneous Ab‐drug conjugates.